The Role of Traffic Community Education in Preventing Traffic Accidents in The Jurisdiction of Muara Enim Police Department - Agum Marenra (Advances in Police Science Research Journal, 2021)
This research is motivated by the number of traffic accidents that occur in Muara Enim Regency. Based on Article 62 letter (d) of the National Police Regulation No. 23/2010, the Dikyasa Unit is tasked with fostering community participation and Traffic Community Education so that the Dikyasa Unit has the responsibility to carry out Traffic Community Education to the people of Muara Enim District. Therefore, a study was conducted that aimed to obtain an overview of traffic accidents in Muara Enim District, analyze the role of Traffic Community Education conducted by the Dikyasa Unit, and describe the factors that affect the implementation of Traffic Community Education activities. The concepts used are the Dikyasa concept, the concept of Traffic Community Education, and the concept of Traffic Accidents. The theories used are the Role theory by Biddle & Thomas, the Management Theory by George R. Terry, and the Communication Theory by Lasswell. This study used a qualitative approach. Data collection techniques used were interviews, observation, and document review. Research location in the jurisdiction of the Muara Enim Departmental Police. The conclusions of this study are known that Description of traffic accidents in Muara Enim District there are 2 (two) main factors causing traffic accidents, particularly human and road factors. The role of Traffic Community Education conducted by the Dikyasa Unit is still lacking in target selection. Factors that affect the Traffic Community Education activities conducted by the Dikyasa Unit is a human factor, in this case, is the number of personnel and qualifications of the Dikyasa unit personnel and the facilities and infrastructure factors. From this study, it is necessary to take repressive actions or strict law enforcement against the public who violate traffic regulations. Advancing cooperation with government agencies related to road improvement and adding street lights and traffic signs in black spot areas. Dikyasa Unit to be more active in social media widely used by people such as Instagram, Facebook, etc. Enhancing the quality of personnel by attending traffic vocational education.